Benchmark study of simulators for thermo-hydraulic modelling of low enthalpy geothermal processes. (November 2021) - Mindel, Julian E.; Alt-Epping, Peter; Landes, Antoine Armandine Les; Beernink, Stijn; Birdsell, Daniel T.; Bloemendal, Martin; Hamm, Virginie; Lopez, Simon; Maragna, Charles; Nielsen, Carsten M.; Olivella, Sebastia; Perreaux, Marc; et al.
Highlights: Ten different state-of-the-art geothermal simulator packages were benchmarked via efforts from seven partners from five different countries. A synthetic test suite was designed for the low-enthalpy range of geothermal operations. The comparative analysis included: COMSOL, MARTHE, ComPASS, Nexus-CSMP++, MOOSE, SEAWATv4, CODE_BRIGHT, Tough3, PFLOTRAN, and Eclipse 100. A confidence-building high-rate of completion and reasonable accuracy was obtained through efforts from all partners, despite 'human factor' effects. Abstract: In order to assess the thermo-hydraulic modelling capabilities of various geothermal simulators, a comparative test suite was created, consisting of a set of cases designed with conditions relevant to the low-enthalpy range of geothermal operations within the European HEATSTORE research project. In an effort to increase confidence in the usage of each simulator, the suite was used as a benchmark by a set of 10 simulators of diverse origin, formulation, and licensing characteristics: COMSOL, MARTHE, ComPASS, Nexus-CSMP++, MOOSE, SEAWATv4, CODE_BRIGHT, Tough3, PFLOTRAN, and Eclipse 100. The synthetic test cases (TCs) consist of a transient pressure test verification (TC1), a well-test comparison (TC2), a thermal transport experiment validation (TC3), and a convection onset comparison (TC4), chosen to represent well-defined subsets of the coupled physical processes acting in subsurface geothermal operations. The results from the four test cases were compared among the participants, to known analytical solutions, and to experimental measurements where applicable, to establish them as reference expectations for future studies. A basic description, problem specification, and corresponding results are presented and discussed. Most participating simulators were able to perform most tests reliably at a level of accuracy that is considered sufficient for application to modelling tasks in real geothermal projects. Significant relative deviations from the reference solutions occurred where strong, sudden (e.g. initial) gradients affected the accuracy of the numerical discretization, but also due to sub-optimal model setup caused by simulator limitations (e.g. providing an equation of state for water properties).